2002
DOI: 10.1074/jbc.m207545200
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally Regulated N-terminal Variants of the Nuclear Receptor Hepatocyte Nuclear Factor 4α Mediate Multiple Interactions through Coactivator and Corepressor-Histone Deacetylase Complexes

Abstract: To understand the mechanisms governing the regulation of nuclear receptor (NR) function, we compared the parameters of activation and repression of two isoforms of the orphan receptor hepatocyte nuclear factor (HNF) 4␣. HNF4␣7 and HNF4␣1 differ only in their N-terminal domains, and their expression in the liver is regulated developmentally. We show that the N-terminal activation function (AF)-1 of HNF4␣1 possesses significant activity that can be enhanced through interaction with glucocorticoid receptor-intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
1
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 66 publications
5
59
1
7
Order By: Relevance
“…It is also consistent with our previous study, where DAX-1 competes with PGC-1␣ for repressing the PPAR␥ transcriptional activity (14). Similar competitions were also observed in the cases of SHP and SMRT, which interact with the same HNF4␣ surface recognized by transcriptional coactivators and competes with them for binding in vivo (47). Although DAX-1, SMRT, and SHP have similar repressive mechanisms for repressing HNF4␣, they are different by competing with coactivator PGC-1␣, GRIP1, and SRC-3, respectively (14,44,47).…”
Section: Discussionmentioning
confidence: 70%
“…It is also consistent with our previous study, where DAX-1 competes with PGC-1␣ for repressing the PPAR␥ transcriptional activity (14). Similar competitions were also observed in the cases of SHP and SMRT, which interact with the same HNF4␣ surface recognized by transcriptional coactivators and competes with them for binding in vivo (47). Although DAX-1, SMRT, and SHP have similar repressive mechanisms for repressing HNF4␣, they are different by competing with coactivator PGC-1␣, GRIP1, and SRC-3, respectively (14,44,47).…”
Section: Discussionmentioning
confidence: 70%
“…28,[45][46][47] Indeed, we observed that while PGC1␣ equally potentiates HNF4␣1 and HNF4␣7 transcriptional activity, p160/ SRC1 potentiates only HNF4␣1. This could explain why, although HNF4␣1 and HNF4␣7 bind CAR/ HNF4RE with equal efficiency, hCAR promoter transactivation by HNF4␣1 is much greater.…”
Section: Discussionmentioning
confidence: 73%
“…While there are a few reports on the differential activity of the HNF4␣ isoforms (22,(93)(94)(95), to our knowledge, this is the first in-depth functional comparison of the HNF4␣ isoforms in a colon cancer line. Likewise, while there are reports of interactions between HNF4␣ and TCF4 (12,31,(40)(41)(42)(43)(44)(45), this is the first report to examine the effect of the presence of the HNF4␣ isoforms on TCF4 chromatin binding, identify a potential three-way interaction between HNF4␣, TCF4, and AP-1, and examine in great depth the DNA binding specificity of the HNF4␣ isoforms and TCF4.…”
Section: Discussionmentioning
confidence: 99%